MODERN APPROACHES TO PREVENTION, EVALUATION AND TREATMENT OF COMPLICATIONS ASSOCIATED WITH ENDOVASCULAR CORONARY ARTERY INTERVENTIONS. PART III. LOSS AND MIGRATION OF CORONARY STENTS DURING ENDOVASCULAR INTERVENTIONS (REVIEW OF LITERATURE AND GENUINE CLINICAL OBSERVATIONS) - S. A. Prozorov (Неотложная медицинская помощь)
THE PURPOSE OF THE STUDY. The purpose is an analysis of the frequency, predictors, and approaches of treatment for loss and migration of the stent during coronary interventions.MATERIAL AND METHODS. Stent migration occurred in 4 patients (3 men and 1 woman aged 45–70 years), which accounted for 0.13% of 3081 cases of coronary intervention from January 2010 to December 2013. In 3 cases, interventions were performed in acute condition.RESULTS. In 3 patients, there was an attempt to stent the circumflex artery and in one case – the anterior interventricular artery. In 2 patients, the undeployed stent was not retreived from the coronary bed, in 1 patient, the stent was advanced down and removed from the femoral artery during arteriotomy, and in 1 patient, visualization of the stent was lost after being advanced down to the terminal branches of aorta.CONCLUSIONS. Predictors of loss and migration of coronary stents are: acute condition, a large divergence angle of a vessel and its tortuosity, calcification. Different methods are used to remove the stent: wrapping two guide wires around the stent; advance of a balloon catheter through the stent, its expansion and removal of the stent; extraction using various loops and forceps. When the removal of the stent is impossible, the «crush» method may be used. By moving the stent into the distal bed further complications usually does not occur.